Pelatihan dan Pendampingan Pembelajaran Calistung dalam Meningkatkan Keterampilan Dasar Siswa Kelas 1 di SDN Kalitimbang II - Annisa Annisa; Merlin Dwi Nova; Sofi Yuliyanti; Siti Nurhayati; Tiara Nofiana; Slamet Gunadi; Yolla Sukma Handayani; Asih Setyo Rini (Jurnal Kabar Masyarakat, 2024)
This research aims to evaluate the effectiveness of training and mentoring in calistung learning (reading, writing and arithmetic) in improving basic skills in lower grade students at SDN Kalitimbang II. Using qualitative research methods, this research involved grade 1 students, as well as their teachers and parents. Data was collected through classroom observations, in-depth interviews with teachers and parents, as well as analysis of student learning outcomes before and after the intervention. The research results showed that calistung training and mentoring significantly improved students' basic skills. This improvement is reflected in better learning outcomes, increased interest in learning, and active participation in learning activities. These findings indicate that calistung training and mentoring is an effective strategy in improving the basic skills of lower class students.